Dampak Covid-19 terhadap Tingkat Kecemasan dan Kinerja Keluarga Peternak Sapi Potong pada Peternakan Rakyat di Provinsi Nusa Tenggara Barat - Dina Oktaviana; Mashur Mashur (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Data on the development of the Covid-19 pandemic as of May 17 2020 shows that all areas in West Nusa Tenggara Province are declared as red zones. This condition causes people to become anxious. One community group that feels this anxiety is beef cattle breeders on smallholder farms. The purpose of this study was to determine the impact of the Covid-19 pandemic on the anxiety level of beef cattle farming families on smallholder farms in West Nusa Tenggara Province. The research method is a survey method from May to September 2022 in 10 regencies/cities throughout West Nusa Tenggara Province. There are 20 parameters that are measured as indicators of anxiety levels. Anxiety levels are measured with a Likert scale of 1-5. Data was tabulated using Microsoft Excel and then analyzed descriptively. The results showed that the impact of the Covid-19 pandemic was most felt by the farmers' wives with an average anxiety level of 97.4%; farmer's children 94.0%; and father as the head of the family 93.3%. The performance of beef cattle breeders is measured by seven indicators showing that 81.5% of beef cattle raising families do not stay at home all day long, but 70.4% leave the house to work in the fields, gardens and fields, and earn a living for their families. The conclusion is that all members of the beef cattle farmer's family feel anxious about the Covid-19 pandemic. The farmer's wife is the member of the family who feels the most anxiety. Nonetheless, the Covid-19 pandemic did not have a negative impact on the performance of beef cattle farming families on smallholder farms in West Nusa Tenggara Province.